2020
DOI: 10.3390/ijerph17020553
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Characteristics of Volatile Organic Compounds and Contribution to Ozone Formation in a Coking Wastewater Treatment Plant

Abstract: Ozone pollution, which can be caused by photochemical reactions, has become a serious problem. The ozone formation potential (OFP) is used to describe the photochemical reactivity. Volatile organic compounds (VOCs) are main precursors of ozone formation, and wastewater treatment plants (WWTPs) are important sources of VOCs. Therefore, it is necessary to study the concentration level and OFP of VOCs from WWTPs. In this work, a coking WWTP with anaerobic-oxic-oxic (A/O/O) processes in Shaoguan city, Guangdong pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…Chloroform, 1,2-dichloropropane and VC at the industrial and urban areas in Thailand were found to be at acceptable levels, according to the local standards of ambient air quality (Average standard, 57, 82 and 20 µg/m 3 , 24 h, respectively) (Sakunkoo et al, 2021). Additionally, methylene chloride, chloroform, tetrachloroethene, trichloroethene, chlorobenzene, and 2-chlorotoluene liberate from the treatment plants of wastewater to the air (Zhang et al, 2020). Trichloroethylene is one of the most common compounds found in indoor environments in China (Dai et al, 2017).…”
Section: Cvocs In Ambient Airmentioning
confidence: 96%
“…Chloroform, 1,2-dichloropropane and VC at the industrial and urban areas in Thailand were found to be at acceptable levels, according to the local standards of ambient air quality (Average standard, 57, 82 and 20 µg/m 3 , 24 h, respectively) (Sakunkoo et al, 2021). Additionally, methylene chloride, chloroform, tetrachloroethene, trichloroethene, chlorobenzene, and 2-chlorotoluene liberate from the treatment plants of wastewater to the air (Zhang et al, 2020). Trichloroethylene is one of the most common compounds found in indoor environments in China (Dai et al, 2017).…”
Section: Cvocs In Ambient Airmentioning
confidence: 96%
“…In advanced oxidation processes, ozone has strong oxidability and fast reaction speed and causes no secondary pollution to the environment. Therefore, ozone is widely used in drinking water treatment [66,67], printing and dyeing wastewater treatment [6,13,68] and coal chemical wastewater [69][70][71]. Ozone can decompose in water to produce stronger oxidizing substances than itself, such as hydroxyl radicals, which can effectively oxidize and degrade organic pollutants in water [9].…”
Section: Ozone Micro/nanobubble Technologymentioning
confidence: 99%
“…VOCs can be a potential risk to the environment and human health. Exposure to high concentrations of VOCs, such as benzene and toluene which can lead to serious health risks (immune, nervous, and reproductive systems, and lead to several types of cancers) [1]. There are different sources of VOCs, however, concerns over VOCs emissions from wastewater treatment plants (WWTPs) into the environment have increased because WWTPs are considered to be one of the major sources of VOC emissions in different countries [2].…”
Section: Introductionmentioning
confidence: 99%